Pengembangan Agrowisata Berbasis Masyarakat pada Usahatani Terpadu guna Meningkatkan Kesejahteraan Petani dan Keberlanjutan Sistem Pertanian - Tati Budiarti; . Suwarto; Istiqlaliyah Muflikhati (Institut Pertanian Bogor, 2013)
Agricultural areas in Western Bandung Regency continue to face the threat due to land area reduction. Development of rural community-based agritourism is expected to benefit not only for rural communities but also urban communities to better understand, providing appreciation, as well as being a means of agriculture education. The factors that determine the development of agritourism, integrated farming systems, local institutional patterns, and the existing program would give a formulation of community-based agritourism development model that is oriented to added value and sustainability of agricultural systems. Assessment on sustainability of the communities in Cikahuripan and Cihideung villages in terms of social and spiritual aspects show good values towards sustainability while the ecological aspects requires corrective actions.